PENGETAHUAN, SIKAP DAN DUKUNGAN SUAMI TERHADAP PERAWATAN LUKA PERINEUM PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI PEKANBARU - Tengku Hartian Silawati Ningsih; Mustika Hana Harahap (Universitas Batam, 2022)
The postpartum period is a period of recovery for the mother's condition. During the puerperium, perineal wounds must receive good treatment so that infection does not occur because improper perineal care can result in perineal conditions that are affected by lochia and moist will greatly support the proliferation of bacteria that can cause infection in the perineum. Wound healing in perineal tears will heal varies, some recover normally and some experience delays in healing, this can be influenced, including the characteristics of the mother in labor, nutritional status, wound conditions, treatment and various other factors.Porpose: to determine the relationship between knowledge, attitudes and husband's support for postpartum mothers regarding wound care in the Payung Sekaki Public Health Center Pekanbaru.This type of research uses observational analytic. This research was conducted on postpartum mothers with perineal wounds, and the sampling technique was purposive sampling with a total sample of 86 respondents. Chi square test analysis, obtained the value of Exact Sig. (2-sided) with a knowledge p value of 0.011, attitude with a p value of 0.020 and husband's support a p value of 0.081.There is a significant relationship between the level of knowledge about wound care and the wound healing process. There is a significant relationship between attitudes about wound care and the wound healing process and there is no significant relationship between husband's support regarding wound care and the postpartum wound healing process, with a Chi Square statistical test with a p value of 0.081.